Multidisciplinary mental health practice : student placement workbook. - Morrissey, Shirley; Davidson, Graham; McAllister, Margaret; McAuliffe, Donna; McConnell, Harry; Reddy, Prasuna (Australian Learning and Teaching Council (ALTC), 2010)
Student placement workbook emanating from a project that explored a distributed leadership approach to cross-disciplinary education and training for mental health practitioners who will take up multidisciplinary mental health placements. The research team investigated the extent to which cross-disciplinary education and training occurs between mental health disciplines in Australian universities. They examined the barriers and challenges that universities face when attempting to facilitate cross-disciplinary learning activities. Those barriers include: insufficient support and resources from universities for cross-disciplinary education; insufficient support from schools of psychology, nursing, social work, occupational therapy, and medicine for cross-disciplinary education; emphasis from professional accreditation bodies on disciplinary integrity and the resultant potential for curriculum overcrowding; and the absence of guidelines, clear philosophical underpinnings, and suitable curriculum approaches and materials to support cross-disciplinary education.